Guía docente para el aprestamiento de la lecto-escritura en achuar propuesta metodológica para la educación inicial - Sanchim Kayap, Rosa Martha (2018)
The work is done for the teachers of the Achuar nationality of Ecuador, especially for those who work in initial education with children from 3 to 4 years old. It is a guide for reading and writing readiness in your language. It will serve as supporting text, so that teachers can use it as support for the teaching-learning process. The teaching guide is made according to the reality of the world of Achuar children, since it includes activities of gross motor skills, fine motor skills, oral language, notions of size, spatial notions, temporal notions, established in the context of cultural context, each one of them contains activities developed in the Achuar language so that the teacher works with the children. The guide is also written in Achuar for teachers to access a material in their own language.